Effect of methotrexate and doxorubicin cumulative doses on superoxide dismutase levels in childhood acute lymphoblastic leukemia - Khalida Fetriyani Ningsih; Sri Mulatsih; Sasmito Nugroho (Indonesian Pediatric Society, 2015)
Background Acute lymphoblastic leukemia (ALL) is the mostcommon malignancy in children. Chemotherapeutic drugs forALL such as methotrexate (Mtx) and doxorubicin producereactive oxygen species (ROS), a type of free radical. The ROScan reduce levels of antioxidants in the body, including superoxidedismutase (SOD). Decreased SOD levels can cause DNA, lipid,and protein damage, which in turn may lead to adverse effectsand treatment failure.Objective To determine the effect of Mtx and doxorubicincumulative doses on SOD levels in children with ALL.Methods We conducted a retrospective cohort study in childrenwith ALL who underwent chemotherapy in Dr. Sardjito Hospitalin October 2011 who had completed the induction phase. Riskfactors for decreased SOD levels were analyzed by Cox regressionand hazard ratio, with a significant level of P <0.05.Results Of 40 patients enrolled, Mtx ≥ 3000 mg/m2 significantlydecreased SOD levels (HR 9.959; 95%CI 2.819 to 35.183; P=0.001). However, doxorubicin ≥90 mg/m2 did not significantlydecrease SOD levels (HR 0.59 95%CI 0.194 to 1.765; P=0.34).Conclusion Methotrexate is associated with decreased SOD levelsin children with ALL. However, doxorubicin is not associated withdecreased SOD levels in the same patient population.